FRI0400 Right ventricular function by 3d-echocardiography and 2d- speckle tracking in scleroderma patients without pulmonary hypertension. (23rd January 2014) - Pigatto, E.; Peluso, D.; Rizzo, M.; Zanatta, E.; Muraru, D.; Favaro, M.; Badano, L.; Punzi, L.; Cozzi, F.
Abstract : Background: Right ventricular (RV) involvement in Systemic Sclerosis (SSc) is usually related to the appearance of pulmonary hypertension (PH). It's unknown if SSc can directly affect RV function in absence of PH. Recently, new more accurate echocardiographic techniques, as 3-dimensional echocardiography (3DE) and 2-dimensional speckle tracking (2DSTE), have been introduced, for better assessment of RV function and mechanics in comparison to standard echo. Objectives: The aim of this study was to use 3DE and 2DSTE, in both SSc patients and sex and age-matched healthy subjects, to identify early echo markers of RV impairment. Methods: Thirtyone SSc patients (29 female and 2 male), mean age 56±11 years and mean SSc duration 13.6±9.4 years, without known heart disease and PH, were studied. Twentyone patients were affected by limited and 10 by diffuse cutaneous form of SSc; ANA were positive in all patients, with anti-centromere specificity in 12 cases, Scl-70 in 10 and without specific ANA in 9. Thirtysix age and gender-matched healthy subjects were enrolled as controls. All subjects underwent a complete echocardiogram, including RV volumes and ejection fraction measured by 3DE dataset. In addition, we measured global and regional longitudinal strain by 2D-speckle tracking method from a dedicated apical view of the RV. Results: RV end-diastolic area and fractional area change were similar in SSc and control subjects; conversely, end-systolic area was larger in SSc patients (9±2.2 vs 8.1±1.4, p=0.045). TAPSE (23±3 vs 26±3, p=0.001) and S wave of RV free wall (13±2 vs 15±3, p=0.004) were lower in SSc patients than in controls. Pulmonary artery systolic pressure (28±6 vs 22±5, p=0.001) and pulmonary vascular resistance (1.7±0.3 UW vs 1.5±0.3 UW, p=0.011) were higher in SSc patients than in controls, without reaching cut-off values for PH diagnosis. End-diastolic volume was similar in SSc and controls (88±22 vs 85±14, p=0.53); conversely, end-systolic volume was larger (43±11 ml vs 33±7 ml) and ejection fraction was lower (51±5% vs 61±6%) in SSc compared to controls (p<0.0001). However, using 2DSTE we found no differences about RV global (-25.6±2.9% vs -25.5±2.8%, p=0.84) and free wall longitudinal strain (-30.3±4.9% vs -31.1±3.6%, p=0.51) between SSc patients and controls. No significant differences about mentioned echocardiographic parameters were found among the different subsets of SSc patients. Conclusions: 3DE evaluation showed an impairment of RV pump function, in term of ejection fraction, in SSc patients, without impairment of myocardial mechanics as assessed by longitudinal deformation (strain). Our data suggest that RV ejection fraction impairment in SSc patients without PH could be related to slightly increased afterload, in presence of preserved RV myocardial function. Disclosure of Interest: None Declared